OPTIMALISASI BANK SAMPAH DUSUN DELIK DENGAN INTEGRASI SIGEMAS (SISTEM INFORMASI GERAKAN MASYARAKAT PEDULI SAMPAH) DALAM PENGELOLAAN SAMPAH - Adityo, R. Dimas; Safrina Alya, Azwa; Maulidia Wachidatus Soli’kha, Maulidia (LPPM Universitas Bhayangkara Surabaya, 2024)
Waste Bank is one of the useful methods to reduce the adverse effects of waste accumulation on the environment. This study tries to optimise the Waste Bank of Delik Hamlet by incorporating the waste care community movement system into the waste management system. The purpose of this study is to see how the incorporation of this system impacts on how well waste management through the Waste Bank in Delik Hamlet. Documentation analysis, interviews, and observations were used in the research. The research shows that combining various programmes of the waste care community movement can increase community participation, waste collection, and briquette making from managed waste. This study provides practical guidelines and suggestions for managing waste banks with a community engaged approach.